Genomic characterization of the rotavirus G3P[8] strain in vaccinated children, reveals possible reassortment events between human and animal strains in Manhiça District, Mozambique - Manjate, Filomena; João, Eva D.; Mwangi, Peter; Chirinda, Percina; Mogotsi, Milton; Messa, Augusto; Garrine, Marcelino; Vubil, Delfino; Nobela, Nélio; Nhampossa, Tacilta; Acácio, Sozinho; Tate, Jacqueline E.; et al. (Frontiers in Microbiology, 2023)
Mozambique introduced rotavirus vaccine (Rotarix®; GlaxoSmithKline Biologicals, Rixensart, Belgium) in 2015, and since then, the Centro de Investigação em Saúde de Manhiça has been monitoring its impact on rotavirus-associated diarrhea, and the trend of circulating strains, where G3P[8] was reported as the predominant strain after vaccine introduction. Genotype G3 is among the most commonly detected RVA strains in humans and animals, and herein, we report the whole genome constellation of G3P[8] detected in two children (aged 18 months old), hospitalized with moderate-to-severe diarrhea at the Manhiça District Hospital. The two strains had a typical Wa-like genome constellation (I1-R1-C1-M1-A1-N1-T1-E1-H1) and shared 100% nucleotide (nt) and amino acid (aa) identities, in 10 gene segments, except VP6. Phylogenetic analysis demonstrated that genome segments encoding VP7, VP6, VP1, NSP3 and NSP4 of the two strains clustered most closely with porcine, bovine, and equine strains with identities ranging from 86.9%-99.9% nt and 97.2-100% aa. Moreover, they consistently formed distinct clusters with some G1P[8], G3P[8], G9P[8] G12P[6], and G12P[8] strains circulating from 2012-2019 in Africa (Mozambique, Kenya, Rwanda and Malawi) and Asia (Japan, China and India) in genome segments encoding six proteins (VP2, VP3, NSP1-NSP2, NSP5/6). The identification of segments exhibiting closest relationships with animal strains shows significant diversity of rotavirus and suggests possible occurrence of reassortment events between human and animal strains. This demonstrates the importance of applying next generation sequencing to monitor and understand the evolutionary changes of strains and evaluate the impact of vaccines on strains diversity.